Cobalt(III)-mediated permanent and stable immobilization of histidine-tagged proteins on NTA-functionalized surfaces - Wegner, Seraphine V.; Schenk, Franziska C.; Spatz, Joachim P. (Chemistry - a European journal, 2016)
We present the cobalt(III)-mediated interaction between polyhistidine (His)-tagged proteins and nitrilotriacetic acid (NTA)-modified surfaces as a general approach for a permanent, oriented, and specific protein immobilization. In this approach, we first form the well-established Co2+-mediated interaction between NTA and His-tagged proteins and subsequently oxidize the Co2+ center in the complex to Co3+. Unlike conventionally used Ni2+- or Co2+-mediated immobilization, the resulting Co3+-mediated immobilization is resistant toward strong ligands, such as imidazole and ethylenediaminetetraacetic acid (EDTA), and washing off over time because of the high thermodynamic and kinetic stability of the Co3+ complex. This immobilization method is compatible with a wide variety of surface coatings, including silane self-assembled monolayers (SAMs) on glass, thiol SAMs on gold surfaces, and supported lipid bilayers. Furthermore, once the cobalt center has been oxidized, it becomes inert toward reducing agents, specific and unspecific interactions, so that it can be used to orthogonally functionalize surfaces with multiple proteins. Overall, the large number of available His-tagged proteins and materials with NTA groups make the Co3+-mediated interaction an attractive and widely applicable platform for protein immobilization.